Mathematical Modelling of Sound Radiation from a T Junction of City Roads in Windy Conditions - PIDDUBNIAK, Olexa; PIDDUBNIAK, Nadia (Archives of Acoustics, 2016)
The sound radiation from vehicles travelling on the city roads with T junction was considered. The wind effect on acoustic field was taken into account. The solution of this problem was found with the help of the integral Fourier transforms and stationary phase method as the superposition of solutions for the cases of vehicles moving along the straight roads and roads with right-angle bend. As an example, the numerical analysis of traffic noise characteristics was carried out for the T junction city road on one of streets in the town of Łódź (Poland).